PENGARUH DARI STRATEGI JIGSAW TERHADAP KEMAMPUAN SISWA TAHUN PERTAMA SMKN 2 KEPENUHAN ROKAN HULU DALAM MEMAHAMI TEKS RECOUNT - Andriyanti, Fitri; Jismulatif, Jismulatif; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This pre-experimental research was aimed to findout whether or not there was a significanteffect of Jigsaw strategy on the ability of the first year students of SMKN 2 Kepenuhan Rokan Huluin comprehending recount text.This research design used one group pre-test and post-test. The sampleofthis research aretakenby using cluster random samplingtechnique and that falls toTata Busana class as big as25 students. The data were collectedby multiple choice tests.The data analyzed by using SPSS 23.00. The result of the data analysis showed that mean scoreof the pre-test was 59.50 and the mean score of post-test was 74.80. In other words, the mean scoreof the post-test was higher than the pre-test. The result also showed that the value of t-test was higherthan t-table (2.49 > 1.71) at significance level of 5%. It can be concluded that Alternative Hypothesis was accepted. Thus, there was a significant effect of jigsaw strategy on the ability of the first year students of SMKN 2 Kepenuhan Rokan Hulu in comprehending recount text. The implication of the findings was that thestudents shouldstudy in group like Jigsaw andmore focus on the given tasks to increase their vocabulary items.KeyWords: Jigsaw, Reading Comprehension, Recount Text